Six-Armed Structures Based on Benzene Ring, Synthesis and Characterization via Sonogashira Coupling - Mohammed Hadi Ali Al-Jumaili; Ahmed Solaiman Hamed; Nihat Akkurt; Lokman Torun (Indonesian Journal of Chemistry, 2020)
A new six-armed compounds consist of benzene ring as a central core substituted with aromatic ring and three rod-like armed of 2-chloro-4,6-bis(dodecyloxy)-1,3,5-triazine as the peripheral arms unit which obtained by sequential nucleophilic substitution of chlorine atoms in cyanuric chloride. The substitution took place at the acetylenic periphery on the central benzene ring by Sonogashira coupling. Equimolar mixtures of the six-armed compounds based on the benzene core with the complementary 4-dodecyloxybenzoic acid, which already possessed liquid crystal property, resulted in an organic salt. The organic salts and structures were investigated by differential scanning calorimetry (DSC), and confirmed by spectroscopic methods (1H-NMR, 13C-NMR and Mass spectroscopy)